Correction: Relevance of COVID-19 vaccine on the tourism industry: Evidence from China. - Fredrick Oteng Agyeman; Zhiqiang Ma; Mingxing Li; Agyemang Kwasi Sampene; Israel Adikah; Malcom Frimpong Dapaah (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0269200.].